Job Security and Organizational Citizenship Behaviors in Chinese Hybrid Employment Context: Organizational Identification Versus Psychological Contract Breach Perspective Differences Across Employment Status - Lu, Wenzhu; Liu, Xiaolang; Liu, Shanshi; Qin, Chuanyan (Frontiers in Psychology, 2021)
The goal of the present research was to identify the mechanism through which job security exerts its different effects on organizational citizenship behaviors (OCB) among contract and permanent employees from social identity and social exchange perspectives. Our research suggests two distinct, yet related explanatory mechanisms: organizational identification and psychological contract breach, to extend the job security literature by examining whether psychological contract breach and organization identity complement each other and explaining the mechanism of different behaviors response to job security across employment status. Data were collected from 211 Chinese employees and 61 supervisory ratings of OCBs. Our results showed that relative to psychological contract breach, organizational identification plays a stronger mediating role in the association between job security and OCBs. Evidence from multi-group analyses also suggested employment status moderated the mediation mechanism of organizational identification between job security and OCB. Implications for job security and hybrid employment management are discussed.